2014
DOI: 10.1097/mpg.0b013e3182a69912
|View full text |Cite
|
Sign up to set email alerts
|

European Pediatricians' Approach to Children With GER Symptoms

Abstract: The overall results of our survey show that the majority of pediatricians are unaware of 2009 North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition-European Society for Pediatric Gastroenterology, Hepatology, and Nutrition reflux guidelines and often prescribe PPIs despite a lack of efficacy for the symptoms being treated. The overdiagnosis of gastroesophageal reflux disease places undue burden on both families and national health systems, which has not been affected by the publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 26 publications
1
24
1
Order By: Relevance
“…The lack of awareness of guidelines on CMPA and the training identified as necessary on this topic has bearing on the recognition and management of this food allergy ( Table 3 ). Our data is supported by a larger study by Hazeldine et al [ 27 ] on GPs’ perceptions of UK allergy care. More than 50% rated allergy care in primary care as poor and 40% reported that they would benefit from more training.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The lack of awareness of guidelines on CMPA and the training identified as necessary on this topic has bearing on the recognition and management of this food allergy ( Table 3 ). Our data is supported by a larger study by Hazeldine et al [ 27 ] on GPs’ perceptions of UK allergy care. More than 50% rated allergy care in primary care as poor and 40% reported that they would benefit from more training.…”
Section: Discussionsupporting
confidence: 88%
“…Although it may be perceived as a problem unique to the UK as GPs are the first point of contact for the recognition of CMPA, data implies that there are similar knowledge barriers for paediatricians worldwide. Quitadamo et al published in 2014 a result from a survey that evaluated the knowledge about gastro-oesophageal reflux guidelines and found that the majority of the paediatricians were unaware of the 2009 guideline from ESPGHAN and the North American Society for Pediatric, Gastroenterology, Hepatology and Nutrition [ 27 ]. In 2014, Maslin et al [ 28 ] published a survey on food allergy competencies amongst UK, Australian and USA dietitians, and found a similar trend in physicians with a need to increase their knowledge in different aspects of food allergy diagnosis and management, specifically the areas of developing food challenge protocols and management of feeding problems.…”
Section: Discussionmentioning
confidence: 99%
“…In infants with troublesome symptoms of GER, when a conservative approach has failed, an alginate-based formulation should be preferred to acid inhibitors. These acid inhibitors continue to be over-prescribed despite their cost, the very limited clinical evidence of reducing GER symptoms in this age group, and the possible adverse effects [29].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it has been widely recommended that GAI treatment in infants should be reserved for cases with evidence of pathological exposure to acid reflux episodes and/or oesophagitis[1]. Despite these recommendations, studies have found very poor adherence to guidelines and significant overtreatment with PPIs[15]. There is a concerning increase in the use of pharmacological intervention using acid suppression therapy using PPIs and H2RAs in preterm infants, with a presumed diagnosis of GORD based on symptoms alone in the absence of any objective measures for the diagnosis of GORD including pH and impedance monitoring or gastroscopy and biopsy[5].…”
Section: Gastric Acid Inhibitor Use In Infantsmentioning
confidence: 99%